THE EXPRESSION OF SUBALI'S STRUGGLE IN THE DANCE WORK "SUBALI GAMAJAYANTI" THROUGH MULTIMEDIA FORM IN DRAMATIC DANCE - Aji, Priyo Bekti Asmoro; Dwi Sasanadjati, M.Hum., Dra. Jajuk Dwi Sasanadjati, M.Hum. (Solah, 2025)
The dance work "Subali Gamajayanti" adopts the story of Subali from the Ramayana epic, portraying him as a steadfast ruler and elder brother who upholds the honour of his family and homeland. This work explores dramatic dance, combining the collaboration between dance and wayang (shadow puppetry) to enhance the narrative, dramatic level, and atmosphere in each scene. The creation of "Subali Gamajayanti" employs Jacqueline Smith's Construction I method with the Construction 1 approach, starting from initial stimuli, exploration, improvisation, evaluation, and refinement. The creation process also involves supporting elements such as multimedia usage, dance accompaniment, makeup, costumes, props, stage decoration, and lighting. The result is a dance work inspired by the visual and narrative elements of the “Wayang Kulit” Subali story from the Ramayana epic, utilising the Construction I method with Jacqueline Smith's double cone dramatic design. The dance movements adopt the Mataraman style and the characteristics of putra gagah (brave male), featuring three dancers and 26 movement patterns lasting 9.30 minutes. This work conveys messages of struggle, solidarity, and courage in facing challenges that threaten the nation's existence. Overall, this piece presents a variety of visual, audio, narrative, and artistic forms, aimed at inspiring the audience to reflect on important values of struggle in life.